Pelatihan Pengolahan Menu Seimbang bagi Keluarga Beresiko di Kabupaten Blora - Anita Lufianti; Mika Agustiana; Nurya Kumalasari; Laily Himawati; Rizki Sahara; Christina Nur Widayati; Yesita Ragil Kusumaningrum; Rahmawati; Fitriani; Yuwanti; Nurulistyawan Tri Purnanto (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2023)
Background: One of the nutritional problems in Indonesia that has become a priority for the national program is stunting. Stunting, a condition where the child's height does not match the child's age, and the condition of stunting in children can have an impact on their growth and development in the future.   Purpose: This community service aims to provide training on processing a balanced menu for at-risk families in Blora Regency   Method: This community service uses a training method for families at risk of stunting with 200 participants from 10 villages.   Results: This community service activity resulted in an increase in knowledge, participants' skills in processing balanced menus as indicated by good knowledge increased from 23.5% to 72.5%.   Conclusion: Training on menu processing can increase the knowledge and skills of groups at risk of stunting.